2002
DOI: 10.1046/j.1440-1754.2002.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of oral versus intravenous fluid supplementation on serum bilirubin level during phototherapy of term infants with severe hyperbilirubinaemia

Abstract: Severely jaundiced healthy term infants had similar rates of decrease in iSB levels during the first 4 h of intensive phototherapy, irrespective of whether they received oral or intravenous fluid supplementation. However, using the oral route avoided the need for intravenous cannulae and their attendant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…A similar study by Boo et al showed effectiveness of fluid supplementation is reducing serum bilirubin level. 9 Our study provides the fluid deficit along with half of the maintenance requirements by the IV rather than oral route, because the effectiveness of oral rehydration may not be sufficiently reliable and fast in the setting of critical hyperbilirubinemia. One of the mechanisms by which fluid supplementation could have helped is expansion of intravascular volume, leading to slight dilutional lowering of TSB.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study by Boo et al showed effectiveness of fluid supplementation is reducing serum bilirubin level. 9 Our study provides the fluid deficit along with half of the maintenance requirements by the IV rather than oral route, because the effectiveness of oral rehydration may not be sufficiently reliable and fast in the setting of critical hyperbilirubinemia. One of the mechanisms by which fluid supplementation could have helped is expansion of intravascular volume, leading to slight dilutional lowering of TSB.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increased use of LED lights, the beneficial effect of fluid supplementation in neonates without dehydration becomes questionable, as LED lights have a much lower heat output and therefore less insensible water loss [12,14]. Intravenous fluid support has no effect on the rate of decrease in serum bilirubin and decrease in duration of phototherapy in healthy term newborns with no dehydration [22,23].…”
Section: Fluid Supplementation/hydrationmentioning
confidence: 99%
“…Till date three trials have evaluated the role of fluid supplementation in neonatal jaundice [5,7,8] Table 3 Multiple logistic regression analysis G6PD glucose 6 phosphate dehydrogenase extracted the raw data from two previous trials [5,8] for the present study as they had same eligibility criteria and protocol for fluid supplementation. The protocol of fluid supplementation in the third trial [7] was different from both the included trials. The authors could identify only 17 Non-responders in both the trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, when full term neonates with severe hyperbilirubinemia were given fluids in addition to phototherapy, the serum bilirubin decreased much faster [7]. The authors have previously shown the effects of intravenous (IV) fluid supplementation in full term neonates with severe non-hemolytic hyperbilirubinemia in two randomized controlled trials (including one unpublished data) [5,8].…”
Section: Introductionmentioning
confidence: 99%